2022
DOI: 10.21315/mjms2022.29.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Induces in vitro Alkalinisation of the Digestive Vacuole in Drug-Sensitive Plasmodium falciparum Strain

Abstract: Background: Malaria is one of the leading causes of death worldwide caused by parasites of the genus Plasmodium. The reduced efficacy of the mainstay antimalarial drugs due to the widespread of drug-resistant Plasmodium falciparum (P. falciparum) necessitates an effort to develop novel antimalarial drugs with new targets. The effects of a phenolic compound, ellagic acid, against the malaria parasite have previously been reported. This present study aimed to evaluate the effect of ellagic acid on pH of the P. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Furthermore, Soh et al reported that ellagic acid suppresses parasitemia in a dose-dependent manner with 100% suppression in mice treated with 50 and 100 mg/kg via the intraperitoneal route [ 62 ]. Previous studies supported the idea that ellagic acid altered the pH of the digestive vacuole through the prevention of proton pumps that control the acidification of this organelle [ 63 ]. In conclusion, the ethanolic extracts of A. lancea and Prabchopoothaweep remedy monotherapy inhibit parasitemia progression, whereas a combination of artesunate (standard drug) and crude extracts from Prabchompoothaweep remedy significantly exerts a potent synergistic effect in the antimalarial property.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, Soh et al reported that ellagic acid suppresses parasitemia in a dose-dependent manner with 100% suppression in mice treated with 50 and 100 mg/kg via the intraperitoneal route [ 62 ]. Previous studies supported the idea that ellagic acid altered the pH of the digestive vacuole through the prevention of proton pumps that control the acidification of this organelle [ 63 ]. In conclusion, the ethanolic extracts of A. lancea and Prabchopoothaweep remedy monotherapy inhibit parasitemia progression, whereas a combination of artesunate (standard drug) and crude extracts from Prabchompoothaweep remedy significantly exerts a potent synergistic effect in the antimalarial property.…”
Section: Discussionmentioning
confidence: 84%
“…New findings confirmed these results. Hence, ellagic acid, the phenolic compound found in oak galls, presented strong antimalarial activity similar to a standard drug, artemisinin, while the pH of the digestive vacuole of ellagic-acid-treated parasites was significantly altered (pH = 6.11 to 6.74, p < 0.001) in a concentration-dependent manner versus untreated parasites [107].…”
Section: Antimicrobial Activitymentioning
confidence: 90%
“…A recent study by Muchtar et al [23] reported one of the mechanisms of action of ellagic acid as acting through the pH of the P. falciparum digestive vacuole. Our group recently reported that polyphenolic derivatives, analogues of ellagic acid, constitute a promising scaffold that could play crucial role in malaria treatment through a currently unknown mode of action [24].…”
Section: Introductionmentioning
confidence: 99%